KOMPETENSI KERJA, IKLIM ORGANISASI, DAN PENEMPATAN PEGAWAI - Romi Pasrah; Meyzi Heriyanto (Universitas Riau, 2013)
The research wasmotivated by the placement officer job in question many people, especially those that occur atpositions in the district. This study examined in Pekanbaru city in order to determine competencypenaruh working toward district employees and job placement to determine the employment climateorganisais employees and analyze the influence of organizational climate and job competencies tostaffing districts in the city of Pekanbaru. Survey method used in this study to all employees in thecity of Pekanbaru district and set 64 people in the sample. The results proved that the competenceof district employee positive and significant (0.05 <0.05) on the implementation of the placement ofcivil servants who were executed by the government of the city of Pekanbaru to district employees,which means that the more competent the district employees better placement.